Enhanced tunability of the multiphoton absorption cross-section in seeded CdSe/CdS nanorod heterostructures - Xing, Guichuan (2011)
We present a method to separately tune the multiphoton absorption (MPA) and multiphoton excited photoluminescence using semiconductor core/enlarged-shell quantum dots (QDs), where the enlarged shell greatly enhances the MPA cross-sections while varying the core size facilitates emission wavelength selectivity. Following two-photon absorption (2PA) primarily in the shell and ultrafast charge-carrier localization to the core, luminescence occurs. We exemplify the validity of this method with CdSe/CdS nanorod heterostructures and find that the 2PA cross-section is enlarged to ∼ 1.4×10^6 GM for 180 nm nanorods (with 800 nm, 150 fs laser pulse excitation) which is two to four orders larger than that of CdSe QDs.